Consultative Workshop on the Co-development of National Framework for Weather, Water and Climate Services (NFWWCS) for the Southern Africa sub-region - Amha, Yosef; Recha, John W.M.; Demissie, Teferi Dejene; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
A three-day experience-sharing workshop was held in Cape Town, South Africa, from 28 to 30 September 2022 to support the co-development of National Framework for Weather, Water and Climate Services (NFWWCS) for the Southern Africa countries. This workshop is a follow-up on the successful co-development and endorsement of AICCRA-supported National Framework for Climate Services (NFCS) in Ethiopia and the subsequent two regional workshops for IGAD and SADC member States held in Zanzibar and Kampala to explore regional landscape in the development and implementation of NFWWCS. The representatives presented their progresses on the planning and development of the NFWWCS, types of weather and climate services offered by their NMHSs and the experiences, lessons learnt, and best practices in the development of the NFWWCS. The progresses were reported in accordance with the Global Framework for Climate Services (GFCS) step-by-step guidelines for NFCS. Strategic and operational challenges faced by the countries including gaps and barriers that inhibits the successful development and implementation of the NFWWCS were discussed. Further to the presentations made by the Southern Africa countries, round table discussions groups were organized in the form of breakaway sessions to surface and deep dive into common challenges, experiences, gaps and barriers to the successful planning and development and implementation of the NFWWCS. The outcome of each working group was presented to the broader participating audience. The audience pondered on solutions that could bridge the gaps that exists in Southern Africa countries that lead to NFWWCS development paralysis. The workshop was concluded by a methodical summarization of the challenges, interventions and way forward proposed for each of the country. The interventions and way forward included country specific solutions that could empower each country, in particular those that are at step zero, to get going while those that have started to progress to the next stages of the NFWWCS development. Common challenges across all Southern Africa countries are associated with lack or limited financial resources to fund the development of the NFWWCS, lack of support and buy-in from national government and political leaders in the respective countries and participation on staff members who are not decision makers. Broader requests included the need to develop a regional framework for weather, water, and climate services, that will drive regional programmes (funding, research, etc.) and assist in accelerating the implementation of NFWWCSs across all the SADC countries. Participants from the Southern Africa countries commended the relevance of this platform and recommended that the support should continue ad infinitum to ramp the development of NFWWCS across all countries. Accordingly, countries at stage zero or stage one requested to have such platform where they can learn more from the Accelerating Impacts of CGIAR Climate Research for Africa in Eastern and Southern Africa (AICCRA ESA) program’s experience in Ethiopia and elsewhere. The AICCRA and its regional collaborating partners’ – the African Climate Policy Centre (ACPC), World Meteorological Organization – Regional office Africa (WMO-RoA) and the IGAD Pridiction and Application Centre (ICPAC) – efforts helped NMHSs to successfully plan, develop and implement NFWWCS and its action plan to strengthen their national adaptive capacities. This workshop was attended by representatives from SADC member countries and their partnering organizations.